Displacement and totalisation: a messianic history of international theory - Mansell, Jonathon (2016)
The phenomenon of displacement is a fundamental source of social, political and economic tensions in the contemporary world. Despite this centrality there has been relatively little sustained theoretical engagement with this phenomenon within the discipline of International Relations (IR). In this thesis I will therefore develop a phenomenological approach, drawing on the work of Emmanuel Levinas, in order to explore ways in which the placed experience of ethical proximity is disrupted through logics of spatial mediation. I will then apply this phenomenological approach to a reading of four fundamental narratives of displacement in the western philosophical tradition: Exodus, Odyssey, Crusade and Conquest. Through these narratives, I will argue, that we find a process of the subsumption of place within spatial totalities in which inter-personal relations are mediated in relation to the projects of the totality. Ultimately, I will suggest this process of totalisation has shaped the fundamental structure of modern international theory. I will also suggest, however, that the placidness of everyday life constantly disrupts this totalisation.